Relaksasi Benson Terhadap Penurunan Tingkat Stres pada Lansia - Hafni Van Gobel; Gusti Ayu Putu Putri Ariani; Indri Pakaya (Poltekkes Kemenkes Gorontalo, 2020)
Background: Stress is a part of everyday human life and is a normal symptom in humans. Benson relaxation is the development of a relaxation response method by involving the patient's belief factor, which can create an internal environment so that it can help patients achieve higher health and well-being.Objective: This study aims to determine Benson relaxation on reducing stress levels in the elderly.Methods: The study used a Quasi Experimental design with a Static Group Comparsion research approach. The sample consisted of 16 elderly people. The sampling technique used paired numerical analysis method.Results: Based on the results of the study, it was obtained that the elderly in the treatment group at the time of the pretest had an average stress level of 39.75 with a standard deviation of 4.062. After using the Beson relaxation technique, the average stress level decreased to 27.38 with a standard deviation of 3.523. In the elderly in the control group at the time of the pretest the average stress level was 42.50 with a standard deviation of 2.330. At the time of re-measurement of the average stress level for the same 8 people, the stress level actually increased to 43.38 with a standard deviation of 2.615. In the treatment group, the value of T count = 11.240 and the value of = 0.000. In the control group, the value of T count = -1,000 and the value of = 0.181.Conclusion: There is a significant effect of Benson's relaxation technique on reducing stress levels in the elderly.